PERANAN KEPALA SEKOLAH UNTUK MENINGKATKAN KETERAMPILAN GURU-GURU DALAM MENERAPKAN METODE BERTANYA PADA PEMBELAJARAN DI SD NEGERI 167959 TEBING TINGGI - Harminsyah Harminsyah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The purpose of this school action research is to improve the ability of teachers to use the question and answer method in implementing learning in schools. School action research is focused on a number of teachers who teach in 167959 Tebing Tinggi Elementary School as 29 subjects, as representatives of 167959 Tebing Tinggi Elementary School members. The research instrument used observation, the results of the formation of written evaluation used to measure changes in the ability of teachers after receiving guidance in cycles I and II. After coaching, modeling from the supervisor. Simulators of fellow teachers can be seen the ability of teachers in the first cycle reached 7.6 close to an average of 8. To improve the ability of teachers in the second cycle re-coaching conducted by supervisors through modeling, simulators and the end of the second cycle evaluation of ability tests can achieve success targets 8, 3 Based on this, the supervisory and mastery of the question and answer method in the lesson was good.Keywords: Improve Skills, Asking Methods, Learning.